Glycyrrhizic acid exerts anti-inflammatory effect to improve cerebral vasospasm secondary to subarachnoid hemorrhage in a rat model. (3rd August 2017) - Li, Yi; Sun, Fengbin; Jing, Zhaohui; Wang, Xuhui; Hua, Xuming; Wan, Liang
Abstract: This study aimed to investigate the therapeutic effect of glycyrrhizic acid (GA) on the cerebral vasospasm (CVS) in a rat subarachnoid hemorrhage (SAH) model and to explore the potential mechanism. A total of 44 healthy male rats were randomly assigned into 3 groups: control group ( n  = 12), SAH group ( n  = 16) and GA group ( n  = 16). No treatment was conducted in control group; in SAH group and GA group, experimental CVS was induced using a double-hemorrhage model and then rats were intraperitoneally injected with normal saline and GA at 10 mg/kg, respectively, once daily. Three days later, neurological function was evaluated. Then, animals were sacrificed, and the basilar artery was collected. The inner diameter and vascular wall thickness were determined. Western blotting was employed to detect high mobility group protein B1 (HMGB1) protein expression and RT-PCR to detect the mRNA expression of IL-1β, IL-6, TNF-α, and IL-10 in the basilar artery. GA treatment significantly improved the neurological function following SAH. In GA group, the basilar artery diameter increased markedly and vascular wall thickness reduced significantly when compared with SAH group ( p  < 0.05). HMGB1 protein expression and mRNA expression of IL-1β, IL-6, TNF-α, and IL-10 in SAH group were significantly higher than in control group ( p  < 0.05). However, GA dramatically reduced IL-1β, IL-6, and TNF-α, and further elevated IL-10 expression as compared to SAH group ( p  < 0.05). GA may inhibit HMGB1 expression and subsequent production of inflammatory cytokines to prevent CVS following SAH.